Geospatial Modeling of Agricultural Land Use Change and Its Environmental Implications Using CA–Markov Model in Aceh Besar, Indonesia - Ona Atmarizona Deska; Muhammad Rusdi; Jumadil Akhir (Jurnal Penelitian Pendidikan IPA, 2026)
Agricultural land use change is an important issue in regional development because it has direct implications for food security and environmental sustainability. This study aims to analyze changes in agricultural land use and model the projected changes and environmental implications using a geospatial approach based on Cellular Automata-Markov (CA-Markov) in Aceh Besar Regency, Indonesia. Land use data for 2012, 2018, and 2024 were analyzed using the Geographic Information System and Land Change Modeler. The classification accuracy test showed an overall accuracy value of 95% and a kappa coefficient of 0.95, which indicates an excellent level of accuracy. The results of the analysis of land use changes for the 2012–2024 period show that agricultural land has decreased significantly due to conversion into settlements and shrubs. CA–Markov modeling yields a high validation rate with a Kstandard value of 0.92. The projected land use in 2032 shows that the downward trend of agricultural land is expected to continue if effective control of space use is not carried out. The findings of this study confirm the importance of geospatial modeling as the basis for spatial planning and sustainable agricultural land protection to support the development of environmentally sound regions.